Prospects of Halal Green Tourism in Brunei Darussalam - Sulaiman, Nor Surilawana; Hashim, Norkhairiah (KnE Social Sciences, 2023)
In recent years, there has been a growing interest among academics worldwide in the concepts of halal and green tourism, particularly focusing on sustainability. This trend has created both opportunities and challenges for tourism stakeholders, as there is a strong interest from tourists in both halal and green tourism experiences. Brunei Darussalam, with about 80% of its land covered in primary tropical forest and a significant portion devoted to permanent forests and forest reserves, offers numerous green tourist attractions despite its small size. To gain a comprehensive understanding of the concepts and relevant aspects of halal-green tourism, this study explores the existing literature and theories related to the topic. Using a qualitative approach and secondary data collection, the study provides insights into halal-green tourism in Brunei. Furthermore, a SWOT analysis of the Brunei tourism industry is presented based on the information gathered. The data indicates that Brunei offers an ideal balance of environmentally friendly and halal-friendly services, making it an attractive destination for halal-green tourism. The SWOT analysis serves as a valuable guideline for relevant authorities and policymakers in planning the future development of the country’s tourism industry. Additionally, local travel agencies can utilize this analysis to promote and enhance halal green tourism in Brunei. Keywords: Brunei, green tourism, halal green tourism, halal tourism, SWOT analysis